Pengembangan Media Pembelajaran Berbasis Virtual Class Berbantuan Google Drive - Sohibun, Sohibun; Ade, Filza Yulina (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2017)
University students become the main target of marketing of information technology developers. Based on the results of a survey with random sampling technique on users of wireless fidelity (wi-fi) service and internet service providers on smartphones, there are 98% of physics students use it and 80% of them actively use it to access various social media. Interactive learning media developed and accessible via smartphone but it is not widely used by lecturers and students yet. There is only 14.3% of lecturers who use e-learning. Virtual Class on e-learning is an online learning environment, in the form of web-based, portal or software. Learning in the real world, every participant both lecturers and students must meet the rules agreed upon during the college contract. One of the strategies to improve the independence of study of physics student is through learning media based on Virtual Class assisted by Google drive. Therefore, it is necessary to develop a lesson that can support conventional learning in the classroom. Mahasiswa menjadi sasaran utama marketing para pengembang teknologi informasi. Berdasarkan hasil survei yang dilakukan dengan teknik random sampling pada pengguna layanan wifi dan layanan internet provider pada gawai, terdapat 98% mahasiswa fisika menggunakannya dan 80% diantaranya aktif menggunakannya untuk mengakses berbagai media sosial. Media pembelajaran interaktif banyak dikembangkan dan dapat diakses melalui gawai. Akan tetapi, belum banyak digunakan dosen dan mahasiswa, hanya 14,3 % saja dosen yang menggunakan e-learning. Virtual Class pada e-learning merupakan lingkungan belajar online, berupa berbasis web, portal atau software. Pembelajaran di dunia nyata, setiap peserta baik dosen maupun mahasiswa harus memenuhi aturan yang disepakati saat kontrak kuliah. Salah satu strategi untuk meningkatkan kemandirian belajar mahasiswa fisika adalah melalui media pembelajaran berbasis Virtual Class berbantuan Google drive. Oleh karenanya, perlu dikembangkan pembelajaran yang dapat menunjang pembelajaran konvensional di kelas